2022
DOI: 10.3390/sports10080111
|View full text |Cite
|
Sign up to set email alerts
|

Higher Leg and Trunk Muscle Activation during Balance Control in Copers versus People with Chronic Ankle Instability and Healthy Female Athletes

Abstract: More than 70% of people with ankle sprain experience chronic ankle instability. However, some people are well adapted to this damage (copers) and do not suffer from chronic ankle instability (CAI). This cross-sectional study involved 34 female athletes, who were classified into three groups (athletes with CAI, copers, and healthy athletes) and tested on a Biodex Balance System. Surface electromyography (EMG) and balance scores were monitored. The coper and healthy group exhibited higher medial gastrocnemius (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…They found increased deltoid and abdominal activity on the less stable Swiss ball, suggesting greater core and limb stability activation. Other studies have shown similar results using plank exercise [21], balance boards [22], and Bosu or Swiss ball exercise [12][13][14]. However, just activating core musculature may not result in improvements in postural control.…”
Section: Introductionmentioning
confidence: 76%
“…They found increased deltoid and abdominal activity on the less stable Swiss ball, suggesting greater core and limb stability activation. Other studies have shown similar results using plank exercise [21], balance boards [22], and Bosu or Swiss ball exercise [12][13][14]. However, just activating core musculature may not result in improvements in postural control.…”
Section: Introductionmentioning
confidence: 76%